2021
DOI: 10.1186/s12870-020-02810-9
|View full text |Cite
|
Sign up to set email alerts
|

GmbZIP1 negatively regulates ABA-induced inhibition of nodulation by targeting GmENOD40–1 in soybean

Abstract: Background Abscisic acid (ABA) plays an important role in plant growth and adaptation through the ABA signaling pathway. The ABA-responsive element binding (AREB/ABF) family transcriptional factors are central regulators that integrate ABA signaling with various signaling pathways. It has long been known that ABA inhibits rhizobial infection and nodule formation in legumes, but the underlying molecular mechanisms remain elusive. Results Here, we sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…For example, NFR1 and NFR5 are major nodulation signaling genes in legumes that interact with Nod factors [ 58 , 59 , 60 , 61 , 62 ]. Many studies showed that the interaction of Nod factor receptors (NFRs) with Nod factors is fundamental for early nodule gene expression and nodule organogenesis [ 6 , 63 , 64 , 65 , 66 , 67 , 68 ]. Furthermore, Nodule inception transcription factors, GmNINa and GmNINb , regulate nodule organogenesis and infection thread development [ 55 , 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, NFR1 and NFR5 are major nodulation signaling genes in legumes that interact with Nod factors [ 58 , 59 , 60 , 61 , 62 ]. Many studies showed that the interaction of Nod factor receptors (NFRs) with Nod factors is fundamental for early nodule gene expression and nodule organogenesis [ 6 , 63 , 64 , 65 , 66 , 67 , 68 ]. Furthermore, Nodule inception transcription factors, GmNINa and GmNINb , regulate nodule organogenesis and infection thread development [ 55 , 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Lee et al (2012) reported the accumulation of coumestrol in root nodules. Moreover, recently, Xu et al (2021) reported that the reduction of root nodulation and rhizobial infection upon exogenous ABA application is related to the reduction of isoflavonoid compounds, including coumestrol. As indicated in Figure 3B , the yellow color that appeared throughout the leaf caused by coumestrol application looked similar to the changes that appear in soybean leaves when naturally aged.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, Lee et al (2012) reported the accumulation of coumestrol in root nodules. Moreover, recently Xu et al (2021) reported the reduction of root nodulation and rhizobial infection upon exogenous. Future investigations into the role of coumestrol in senescence, root development, and disease resistance can provide new insights into the roles of this important secondary metabolite.…”
Section: Discussionmentioning
confidence: 99%
“…Members of the bZIP transcription factor family, such as ABRE-binding factor and ABA-insensitive five (AREB/ ABF/ABI5) members, which responses to stress in Arabidopsis (Yoshida et al 2015), rice (O. sativa L.) (Yoshida et al 2010), and soybean (G. max L.) (Xu et al 2021) might regulate stress responses through the ABA signal way, but few study had been reported in common bean. Cloning of IbbZIP1 in sweet potatoes indicated that there might have been the same relationships between the ABA content and salt stress as the transgenic Arabidopsis (Chen et al 2019).…”
Section: Pvbzips Might Have a Potential Connection With Abamentioning
confidence: 99%